From Andean ethnohistory to general ethnology A proposal to a new integrative conceptualization of culture - Arana Bustamante, Luis (2011)
"this paper exposes a proposition to rhe long di scusscd prohlcrn of culture that scck ro combine -rcspccting its more or lcss panicular sphcres ofaction- the diversc fields concomed in human perccption, categorizarion and cognition of natural and social world. It is bascd in obscrvarion and rciiccrion about cultural rransforrnation and chauge of conceptual and preconceprual schcrncs in past and ruodcrn Andean societies, compararion -still preliminar- wuh paralcl aspcCls of Amazon ian socierics and rcllect ion aboui rhc rnodcls and dcfinirions proposcd by rnai n schools of anrhropological rhought, conrributions of psychology and later dcvelopmen ts in rheorerical (usioll bcrwccn anthropological and historical poinrs of view, Sorne aspccts srudicd hy dcpth psicology are considered in rhc gmund (Ir rhis phacnomcna, and also more conremporary devcloprnents in tusion of anrhropological and historical perspecrives, unril now considercd alrnoxt oppositc. Going [urrhcr from lile rhcorcrical aspecto mis proposal has becn framcd as a mcrhodological ground lor a controled comparative analysis or cultural manitestarions in complcx socicries of very long cultural tradit ion as Mcsoamcrican and Andcan civilizarions.